Pendidikan Moderasi Beragama dalam Perspektif Islam: Menjaga Harmoni di Tengah Keberagaman - Fahri Nugraha Syahputra; Rizky Arya Perdana (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2024)
This article explores the concept of religious moderation in the Islamic perspective and how Islamic education can play a role in maintaining harmony amid diversity. Using the literature study method and qualitative analysis, this research shows that moderate Islamic values, such as tolerance, deliberation, and ukhuwah Islamiyah, must be instilled early on through Islamic education. Religious moderation education is proven to be able to prevent radicalism and build an inclusive attitude in social life.